Erector spinae versus paravertebral plane blocks in modified radical mastectomy: Randomised comparative study of the technique success rate among novice anaesthesiologists - Moustafa, Moustafa; Alabd, Ahmad; Ahmed, Aly; Deghidy, Ehsan (Indian journal of anaesthesia, 2020)
Background and Aims: Regional analgesia may play a role in pain management during breast surgery. Ultrasound approach to paravertebral block may be challenging. This study compared success rates of ultrasound-guided erector spinae plane block (ESPB) versus parasagittal in-plane thoracic paravertebral block among senior anaesthesia residents in modified radical mastectomy. Methods: One hundred and two female patients undergoing modified radical mastectomy were randomly categorized into PARA group receiving sagittal in-plane paravertebral block and ESPB group receiving erector spinae plane block. The block in the 1st six cases in each group was done by an experienced consultant as a demonstration for three anaesthesia residents not experienced in either block. Primary endpoint was assessing success rate of the blocks. Secondary endpoint was the haemodynamic response to skin incision and postoperative analgesia. Results: All patients were females undergoing modified radical mastectomy. Success rate among residents was 100% in ESPB versus 77.8% in PARA group (P = 0.002). Duration to perform the block was less in ESPB group (4.39 ± 1.2 min) than PARA group (8.18 ± 2.42 min) (P< 0.0001). Guidance frequency by consultants was significantly higher in PARA than ESPB group. Time to 1st analgesic requirement and morphine consumption postoperatively were insignificant between the groups. There was no significant difference regarding haemodynamics. Conclusion: ESPB may be a simple and safe alternative to parasagittal in-plane paravertebral block to provide postoperative analgesia in modified radical mastectomy especially in novice practitioners. It provides equivalent profile of postoperative analgesia with less time to perform the block.